Breaking habits or breaking habitual behaviours? Old habits as a neglected factor in weight loss maintenance. (1st July 2021) - Gardner, Benjamin; Richards, Rebecca; Lally, Phillippa; Rebar, Amanda; Thwaite, Tanya; Beeken, Rebecca J.
Abstract: Maintaining weight loss requires long-term behaviour change. Theory and evidence around habitual behaviour – i.e., action triggered by impulses that are automatically activated upon exposure to cues, due to learned cue-action associations – can aid development of interventions to support weight loss maintenance. Specifically, weight loss is more likely to be sustained where people develop new habits that support weight management, and break old habits that may undermine such efforts. Interventions seeking to break 'bad' weight-related habits have focused on inhibiting unwanted impulses or avoiding cues. This paper draws attention to the possibility that while such approaches may discontinue habitual behaviour, underlying habit associations may remain. We use evidence from existing qualitative studies to demonstrate that, left unchecked, unwanted habit associations can render people prone to lapsing into old patterns of unhealthy behaviours when motivation or willpower is momentarily weakened, or when returning to familiar settings following temporarily discontinued exposure. We highlight six behaviour change techniques especially suited to disrupting habit associations, but show that these techniques have been underused in weight loss maintenance interventions to date. We call for intervention developers and practitioners to adopt techniques conducive to forming new habit associations to directly override old habits, and to use the persistence of unwanted habit associations as a potential indicator of long-term weight loss intervention effectiveness.